The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/curroncol29100536
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Treatment and Prognosis of Primary Pulmonary NUT Carcinoma: A Literature Review

Abstract: NUT carcinoma is a rare, highly lethal cancer characterized with the rearrangement of the nuclear protein in testis (NUT) gene on chromosome 15q14, which primarily occurs in the midline organs. Primary pulmonary NUT carcinoma (NC) lacks characteristic clinical manifestations, which leads to the high rate of misdiagnose and nonstandard treatment. To date, fewer than one hundred cases have been reported worldwide. Here, a comprehensive literature search involving a total of 35 articles with 55 patients was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In terms of epidemiology, primary pulmonary NMC mainly affected children and young adults, with a median age of 29.5 years (range: 6-74 years), younger than in other reports ( 38 , 40 ). Both genders are equally affected.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In terms of epidemiology, primary pulmonary NMC mainly affected children and young adults, with a median age of 29.5 years (range: 6-74 years), younger than in other reports ( 38 , 40 ). Both genders are equally affected.…”
Section: Discussionmentioning
confidence: 63%
“…cases of pulmonary NMC, with the objective of enhancing our understanding of the epidemiological, pathological, and immunohistochemical features of this disease. In terms of epidemiology, primary pulmonary NMC mainly affected children and young adults, with a median age of 29.5 years (range: 6-74 years), younger than in other reports (38,40). Both genders are equally affected.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Initially, NUT carcinoma was thought to occur more commonly in children and young adults, but recent studies revealed that the tumor could occur at almost any age [28] , with nearly the same incidence in both men and women [25] . And pulmonary NUT carcinoma mainly occurred in young and middle-aged men with no history of smoking (2:1), and the male-to-female ratio was about 1.89 to 1 [29] . He et al.…”
Section: Clinical Characteristicsmentioning
confidence: 99%